Melamine decorative board surface protective film and melamine decorative board

A melamine decorative board surface protection film with a core-shell rubber and controlled resin layers addresses adhesion and water whitening issues, offering improved adhesion and resistance without additional adhesives, thus reducing costs and complexity.

JP2024178685APending Publication Date: 2024-12-25MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023097012
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Existing acrylic resin films for melamine decorative boards suffer from inadequate adhesion and lack water whitening resistance, necessitating the use of adhesives and primers, which increase costs and complexity.

Method used

A melamine decorative board surface protection film comprising a resin layer with a core-shell rubber containing a specific monomer-derived structural unit and an acrylic resin layer with controlled acid value and thickness, allowing for excellent adhesion and water whitening resistance without the need for additional adhesives.

Benefits of technology

The film provides superior adhesion to melamine decorative boards, enhances water whitening resistance, and reduces production costs by eliminating the need for adhesives, while maintaining excellent handling properties and appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178685000001
    Figure 2024178685000001
Patent Text Reader

Abstract

To provide a melamine decorative board surface protective film excellent in adhesion to the melamine decorative board and whitening resistance.SOLUTION: A melamine decorative board surface protective film has a layer (II) made of a resin composition (B), wherein the resin composition (B) contains a core-shell rubber (B-2) containing a constituent unit derived from a monomer expressed by formula 1: CH2=C(R1)COO-R2 (wherein R1 is a hydrogen atom or a methyl group, R2 is a group selected from a hydrogen atom, a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface protective film for melamine decorative boards and a melamine decorative board. [Background technology]

[0002] Since acrylic resin films have excellent transparency and weather resistance and high surface hardness, they are preferably used as films for protecting surfaces by being attached to various molded articles for indoor or outdoor use, such as optical parts of electrical products, interior parts of automobiles, signs, building materials, etc. In addition, by subjecting the surface of the acrylic resin film to a surface treatment such as antireflection treatment or antifouling treatment and then attaching the film to a molded article, it is also possible to impart surface functions such as antireflection and antifouling properties to the molded article.

[0003] When these acrylic resin films for lamination are laminated to a substrate having poor adhesiveness to acrylic resins, the use of adhesives, primers, etc. requires labor and time, which is disadvantageous in terms of cost. For this reason, acrylic resin films that have been given adhesiveness by introducing reactive groups into the acrylic resin film, etc. have been developed.

[0004] For example, Patent Document 1 discloses a film that contains a polymer including a structural unit derived from a monomer having a reactive group, and that has excellent adhesion to a melamine decorative board.

[0005] For example, Patent Document 2 discloses a film that contains a resin layer having a certain acid value and has excellent adhesion to metals. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2014 / 192708 [Patent Document 2] JP 2013-103385 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in Patent Document 1, the adhesion when the film was laminated to the melamine decorative board was insufficient. On the other hand, Patent Document 2 refers to the adhesion to metal, but does not refer to the adhesion to the melamine decorative board. SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a surface protective film for melamine decorative boards which has excellent adhesion to melamine decorative boards and excellent resistance to water whitening, and a melamine decorative board using the same. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that the above object can be achieved, and have completed the present invention. That is, the present invention relates to the following [1] to [8]. [1] A surface protecting film for melamine decorative boards, comprising a resin layer (II) made of a resin composition (B), the resin composition (B) containing a core-shell rubber (B-2) containing a structural unit derived from a monomer represented by the following formula 1: CH2=C(R 1 )COO-R 2 - Formula 1 Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a group selected from a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group. [2] The surface protecting film for melamine decorative boards according to [1], wherein the acid value of the resin composition (B) is 5 mgKOH / g or more. [3] The surface protecting film for melamine decorative boards according to [1] or [2], further comprising a resin layer (I) made of an acrylic resin composition (A) having an acid value of less than 5 mgKOH / g. [4] The surface protecting film for melamine decorative boards according to [3], wherein the maximum height Rz of the resin layer (I) is 0.15 μm or more. [5] The surface protecting film for melamine decorative boards according to [3] or [4], wherein the content of the antiblocking agent in 100 mass% of the acrylic resin composition (A) is 0.01 to 2 mass%. [6] The surface protecting film for melamine decorative boards according to any one of [1] to [5], wherein the resin layer (II) has a thickness of 3 to 10 μm. [7] The surface protecting film for melamine decorative boards according to any one of [3] to [6], wherein the acrylic resin composition (A) contains a core-shell rubber, and the particle size of the core-shell rubber is 100 nm or more. [8] A melamine decorative board comprising the surface protective film for melamine decorative boards according to any one of [3] to [7] and a melamine substrate laminated in the order of resin layer (I), resin layer (II) and melamine substrate. Effect of the Invention

[0009] According to the present invention, it is possible to provide a surface protecting film for melamine decorative boards, which has excellent adhesion to melamine decorative boards and excellent resistance to water whitening, and a melamine decorative board using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Surface protection film for melamine decorative panels] The surface protecting film for melamine decorative boards of the present invention comprises a resin layer (II) made of a resin composition (B). The resin composition (B) contains a core-shell rubber (B-2) containing a structural unit derived from a monomer represented by the following formula 1 in order to exhibit adhesion to a melamine substrate. CH2=C(R 1 )COO-R 2 - Formula 1 Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a group selected from a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group. In the surface protecting film for melamine decorative boards of the present invention, a resin layer (I) made of an acrylic resin composition (A) may be further laminated on the resin layer (II). When the surface protective film for melamine decorative boards of the present invention is a laminate film of resin layer (I) and resin layer (II) (hereinafter referred to as laminate film), when bonding to a melamine substrate, it is preferable that the resin layer (II) made of resin composition (B) is used as the bonding layer facing the substrate, and the resin layer (I) made of acrylic resin composition (A) is used as the surface layer facing away from the substrate.

[0011] [Resin layer (I)] The resin layer (I) of the present invention is made of an acrylic resin composition (A) having an acid value of less than 5 mgKOH / g. The lower limit of the acid value is not particularly limited, but may be 0 mgKOH / g.

[0012] The "acid value" in the present invention is a value determined by general neutralization titration, specifically, by the method described in the Examples below. If any anhydride is present in the resin, it is ring-opened to form an acid, and the total amount of the acid is taken as the acid value. This is because the proportion of the acid that is anhydridized varies greatly depending on the extrusion conditions.

[0013] The maximum height Rz of the resin layer (I) is preferably 0.11 μm or more, more preferably 0.15 μm or more, and even more preferably 0.18 μm or more. If the maximum height Rz of the resin layer (I) is 0.11 μm or more, blocking between films can be prevented when storing the film in sheets for melamine decorative boards, and handling is excellent. The upper limit of the maximum height Rz is not particularly limited, but is, for example, 1.0 μm or less. The maximum height Rz can be adjusted by an anti-blocking agent described later.

[0014] The storage modulus of the resin layer (I) at 100°C is preferably 1 to 1500 MPa, more preferably 1 to 1000 MPa, more preferably 100 to 950 MPa, and even more preferably 500 to 900 MPa. When the storage modulus of the resin layer (I) at 100°C is 1 MPa or more, the heat resistance and surface hardness of the melamine decorative board are good. When the storage modulus of the resin layer (I) at 100°C is 1500 MPa or less, the transferability of the embossed shape is good when the embossed shape is transferred by hot pressing, and a melamine decorative board with good appearance can be produced. Melamine decorative boards are usually made by hot pressing at a temperature of 140 to 160°C, but when many large-area laminates are laminated and pressed at the same time, the temperature may become uneven in some areas, resulting in low-temperature areas of around 100°C. Even in such cases, a melamine decorative board with a good appearance can be obtained as long as the storage modulus at 100°C is 1000 MPa or less. The storage modulus can be measured by the method described in the Examples.

[0015] [Acrylic resin composition (A)] The acrylic resin composition (A) of the present invention preferably contains a core-shell rubber (A-1) from the viewpoints of film productivity and handleability, and may contain, for example, the core-shell rubber (A-1), a thermoplastic polymer (A-2), and an additive (A-3). In particular, the acrylic resin composition (A) preferably contains 5.5 to 95 mass% of (A-1) and 5 to 94.5 mass% of (A-2) relative to 100 mass% of the total of (A-1) and (A-2), and further contains 0.01 to 20 mass parts of additive (A-3) relative to 100 parts by mass of the total of (A-1) and (A-2). If the content of the core-shell rubber (A-1) is 5.5% by mass or more, the resin layer (I) is given more toughness, the film is less likely to break during the production of the laminated film, and the productivity is better. In addition, the handling property of the laminated film during use is good. If the content of the thermoplastic polymer (A-2) is 5% by mass or more, the surface hardness of the resin layer (I) is better.

[0016] The acrylic resin composition (A) preferably contains 10 to 90 mass% of (A-1) and 10 to 90 mass% of (A-2), and more preferably contains 15 to 85 mass% of (A-1) and 15 to 85 mass% of (A-2), relative to 100 mass% of the total of (A-1) and (A-2). The acrylic resin composition (A) more preferably contains 0.1 to 10 parts by mass, and even more preferably 1 to 8 parts by mass, of the additive (A-3) per 100 parts by mass of the total of (A-1) and (A-2).

[0017] [Core-shell rubber (A-1)] The core-shell rubber (A-1) may be a particle having a multilayer structure, and is preferably a rubber particle having a multilayer structure of two or more layers in which a layer containing a hard polymer (a-2) is formed as an outer layer on a layer containing an elastic copolymer (a-1) as an inner layer. Examples of the material for the core-shell rubber include acrylic rubber, silicone rubber, butadiene rubber, etc., and from the viewpoints of transparency and weather resistance, acrylic rubber is preferred. Examples of the acrylic rubber include those similar to those described in Patent Document 1.

[0018] The particle size of the core-shell rubber is preferably 100 nm or more, more preferably 100 to 400 nm, even more preferably 150 to 350 nm, and particularly preferably 200 to 300 nm. When the particle size of the core-shell rubber is 100 nm or more, the surface hardness is better from the viewpoint of being able to reduce the amount of rubber added per unit area. When the particle size of the core-shell rubber is 400 nm or less, the transparency of the film is excellent.

[0019] [Thermoplastic polymer (A-2)] The thermoplastic polymer (A-2) is a thermoplastic polymer other than the core-shell rubber (A-1), and is preferably a polymer obtained by polymerizing a monomer containing an alkyl methacrylate ester as a main component. Examples of the thermoplastic polymer (A-2) include the thermoplastic polymers and polymer-based processing aids described in Patent Document 1.

[0020] [Additives (A-3)] The additive (A-3) is a compound other than the core-shell rubber (A-1) and the thermoplastic polymer (A-2), and examples thereof include an antiblocking agent, a stabilizer, a lubricant, a plasticizer, a foaming agent, a filler, a colorant, and an ultraviolet absorber.

[0021] For example, from the viewpoint of imparting weather resistance to protect the substrate, the additive (A-3) is preferably an ultraviolet absorber. The molecular weight of the ultraviolet absorbent is preferably 300 or more, more preferably 400 or more. If the molecular weight is 300 or more, the ultraviolet absorbent is less likely to volatilize during vacuum molding or pressure molding in an injection mold, and mold staining is less likely to occur. Furthermore, bleeding out of the ultraviolet absorbent after molding is reduced. The ultraviolet absorber is preferably a benzotriazole-based ultraviolet absorber having a molecular weight of 400 or more, or a triazine-based ultraviolet absorber having a molecular weight of 400 or more. From the viewpoint of maintaining ultraviolet shielding ability for a long period of time, a triazine-based ultraviolet absorber having a molecular weight of 400 or more is more preferable.

[0022] Commercially available benzotriazole-based ultraviolet absorbents having a molecular weight of 400 or more include, for example, "Tinuvin 234" (trade name, manufactured by Ciba-Geigy Ltd.) and "Adekastab LA-31" (trade name, manufactured by ADEKA Corporation). An example of a commercially available triazine-based ultraviolet absorbent having a molecular weight of 400 or more is "Tinuvin 1577" (product name, manufactured by Ciba-Geigy). These may be used alone or in combination of two or more.

[0023] The amount of the ultraviolet absorber added is preferably 0 to 20 parts by mass per 100 parts by mass of the total of the core-shell rubber (A-1) and the thermoplastic polymer (A-2) from the viewpoint of weather resistance, and more preferably 1 to 5 parts by mass from the viewpoint of preventing mold contamination during molding or bleed-out.

[0024] In order to further improve weather resistance, it is preferable to use a radical scavenger such as a hindered amine-based light stabilizer in combination with the ultraviolet absorber. Commercially available radical scavengers include, for example, "ADK STAB LA-57", "ADK STAB LA-62", "ADK STAB LA-67", "ADK STAB LA-63", and "ADK STAB LA-68" (all trade names, manufactured by ADEKA CORPORATION); "SANOL LS-770", "SANOL LS-765", "SANOL LS-292", "SANOL LS-2626", "SANOL LS-1114", and "SANOL LS-744" (all trade names, manufactured by Sankyo Lifetech Co., Ltd.). These may be used alone or in combination of two or more.

[0025] The amount of the radical scavenger added is preferably 0 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, per 100 parts by mass of the core-shell rubber (A-1) and the thermoplastic polymer (A-2) in total, from the viewpoint of bleed-out resistance.

[0026] In order to impart an anti-blocking effect, the additive (A-3) is preferably an anti-blocking agent. An example of a commercially available antiblocking agent is "AEROSIL R976" (manufactured by Nippon Aerosil Co., Ltd.).

[0027] The amount of the antiblocking agent added is preferably 0.01 to 2% by mass, more preferably 0.05 to 1.5% by mass, and even more preferably 0.1 to 1.0% by mass, based on 100% by mass of the acrylic resin composition (A). When the content of the antiblocking agent is 0.01% by mass or more, blocking between films can be prevented when storing the film in sheets for use in melamine decorative boards, and handling is excellent. When the content of the antiblocking agent is 2% by mass or less, the decrease in transparency of the obtained film can be suppressed, and the occurrence of fish eyes can be reduced.

[0028] In addition, from the viewpoint of preventing sticking to the press plate when the melamine decorative board is produced by pressing, the additive (A-3) is preferably a release agent. Examples of the release agent include silicone compounds, fluorine compounds, alkyl alcohols, and alkyl carboxylic acids. Among these, alkyl carboxylic acids are preferred from the standpoint of availability and economy. Examples of alkyl carboxylic acids include linoleic acid, vaccenic acid, stearic acid, oleic acid, margaric acid, palmitoleic acid, palmitic acid, and pentadecylic acid. These may be used alone or in combination of two or more.

[0029] The amount of the release agent added is preferably 0.01 to 2 parts by mass, and more preferably 0.1 to 0.5 parts by mass, per 100 parts by mass of the core-shell rubber (A-1) and the thermoplastic polymer (A-2) in total, from the viewpoint of preventing sticking to the press plate.

[0030] [Resin layer (II)] The resin layer (II) of the present invention contains a core-shell rubber (B-2) containing a constituent unit derived from a monomer represented by the following formula 1 in order to exhibit adhesion to a substrate. CH2=C(R 1 )COO-R 2 - Formula 1 Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a group selected from a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group.

[0031] Components constituting the resin composition (B) other than the core-shell rubber (B-2) may include a reactive group-containing acrylic polymer (B-1), a thermoplastic polymer (B-3), and an additive (B-4).

[0032] [Resin composition (B)] The resin composition (B) of the present invention is represented by the following (1) or (2). (1): The composition contains 0 to 99% by mass of (B-1), 1 to 100% by mass of (B-2) and 0 to 99% by mass of the thermoplastic polymer (B-3) relative to 100% by mass of the total of the reactive group-containing acrylic polymer (B-1), the core-shell rubber (B-2) and the thermoplastic polymer (B-3). The composition contains 0 to 99% by mass of the thermoplastic polymer (B-3). Furthermore, the composition contains 0 to 50 parts by mass of the additive (B-4) relative to 100 parts by mass of the total of (B-1), (B-2) and (B-3). (B-1) and (B-2) contain monomer units having a reactive group with respect to an amino group or a methylol group. The content of the monomer units having a reactive group with respect to 100% by mass of the total of (B-1), (B-2) and (B-3) is 1.5% by mass or more. The glass transition temperature (Tg) of (B-1) is preferably 60 to 120°C.

[0033] (2): It is preferred that the resin composition (B) contains 0 to 99% by mass of (B-1), 1 to 100% by mass of (B-2) relative to 100% by mass of the total of the reactive group-containing acrylic polymer (B-1), the core-shell rubber (B-2), and the thermoplastic polymer (B-3), contains 0 to 99% by mass of the thermoplastic polymer (B-3), and further contains 0 to 50 parts by mass of an additive (B-4) relative to 100 parts by mass of the total of (B-1), (B-2), and (B-3), the acid value of the resin composition (B) is 5 mgKOH / g or more, and the Tg of (B-1) is 60 to 120°C.

[0034] In the above (1) and (2), from the viewpoints of melamine adhesion, film handling property, and scratch resistance, the resin composition (B) preferably contains 0 to 95 mass% of (B-1), 5 to 95 mass% of (B-2), and 0 to 95 mass% of (B-3) relative to 100 mass% of the total of (B-1), (B-2), and (B-3), more preferably contains 0 to 90 mass% of (B-1), 10 to 90 mass% of (B-2), and 0 to 90 mass% of (B-3), and even more preferably contains 0 to 85 mass% of (B-1), 15 to 85 mass% of (B-2), and 0 to 85 mass% of (B-3). Furthermore, the content of (B-4) is preferably 0.1 to 10 parts by mass, more preferably 1 to 5 parts by mass, and even more preferably 2 to 4 parts by mass, per 100 parts by mass of the total of (B-1), (B-2), and (B-3).

[0035] From the viewpoint of melamine adhesion, it is preferable to contain both (B-1) and (B-2) in appropriate amounts. The more (B-1) and (B-2) are contained, the higher the reactive group content is, and the better the melamine adhesion is. Also, the more (B-2) is contained, the more the breakage inside the resin layer (II) is suppressed, and therefore the better the melamine adhesion is. From the viewpoint of film handling properties, the more (B-2) is contained, the more preferable it is. The more (B-2) is contained, the more the toughness of the resin layer (II) is improved, and the more the handling properties of the laminate film are improved. From the viewpoint of scratch resistance, the smaller the amount of (B-2), the more preferable. The smaller the amount of (B-2), the higher the pencil hardness and the more improved the scratch resistance. From the viewpoint of film appearance, the smaller the amount of (B-2), the better. The smaller the amount of (B-2), the more suppressed the generation of gelled matter due to thermal deterioration during melt molding, the less foreign matter there is, and the better the film appearance.

[0036] In the above (1), the content of the monomer unit having a reactive group is preferably 1.5% by mass or more relative to the total 100% by mass of (B-1), (B-2), and (B-3). In addition, the reactive group-containing acrylic polymer (B-1) and the core-shell rubber (B-2) contain a monomer unit having a reactive group with respect to an amino group or a methylol group, and the content is preferably 1.5% by mass or more relative to 100% by mass of the reactive group-containing acrylic polymer (B-1) and 1.5% by mass or more relative to 100% by mass of the core-shell rubber (B-2). By containing 1.5% by mass or more of the monomer unit having a reactive group, good melamine adhesion can be obtained. In order to obtain better melamine adhesion, it is preferable that the monomer unit having a reactive group is contained in an amount of 2% by mass or more, and more preferably 3% by mass or more. The upper limit of the content of the monomer unit having a reactive group is not particularly limited, but it can be, for example, 50% by mass or less. This content is a value calculated from the amount of raw material charged.

[0037] In the above (2), the acid value of the resin composition (B) is 5 mgKOH / g or more. If the acid value is 5 mgKOH / g or more, good melamine adhesion can be obtained. The acid value is preferably 200 mgKOH / g or less. If the acid value is 200 mgKOH / g or less, the water absorption of the resin composition (B) decreases, and the water whitening resistance of the laminated film and the melamine decorative board laminated with the laminated film is improved. From the viewpoint of melamine adhesion and water whitening resistance, the acid value is preferably 10 mgKOH / g or more, more preferably 15 mgKOH / g or more, and even more preferably 20 mgKOH / g or more. On the other hand, it is more preferably 150 mgKOH / g or less, even more preferably 100 mgKOH / g or less, particularly preferably 80 mgKOH / g or less, and most preferably 50 mgKOH / g or less. The acid value is a value calculated by the method described below.

[0038] The content of the monomer unit having a reactive group relative to 100% by mass of the resin composition (B) is preferably 1.5% by mass or more. By containing 1.5% by mass or more of the monomer unit having a reactive group, good melamine adhesion can be obtained. In order to obtain better melamine adhesion, it is preferable to contain 2% by mass or more of the monomer unit having a reactive group, and more preferably 3% by mass or more. There is no particular limit to the upper limit of the content of the monomer unit having a reactive group, but it can be, for example, 50% by mass or less. This content is a value calculated from the amount of raw material charged.

[0039] The gel fraction of the resin composition (B) is preferably 5 to 80%. The higher the gel fraction, the higher the toughness of the film, and the easier it is to handle and form the film. The lower the gel fraction, the more the generation of foreign matter due to thermal degradation of the resin is suppressed, and the better the film appearance. If the gel fraction is 5 to 80%, both the film toughness and the film appearance can be achieved. From the viewpoint of film toughness, the gel fraction is more preferably from 45 to 80%, and further preferably from 50 to 80%. From the viewpoint of the appearance of the film, the gel fraction is more preferably from 5 to 30%, and further preferably from 5 to 25%.

[0040] [Reactive group-containing acrylic polymer (B-1)] The reactive group-containing acrylic polymer (B-1) contains a monomer unit having the specific reactive group described in (1) or (2) above. The reactive group-containing acrylic polymer (B-1) may contain, for example, a monomer unit having a reactive group, an aromatic vinyl monomer unit, and other monomer units. Specifically, the reactive group-containing acrylic polymer (B-1) can contain 1.5 to 100 mass% of monomer units having a reactive group, 0 to 3 mass% of aromatic vinyl monomer units, and 0 to 96 mass% of other monomer units, totaling 100 mass%.

[0041] The reactive group-containing acrylic polymer (B-1) contains a monomer unit having a group reactive to an amino group, such as a carboxyl group, or a methylol group, and therefore can adhere to a melamine decorative board by being heated and reacted in contact with a material containing methylol melamine and its derivatives, specifically, the melamine resin of a melamine decorative board or its precursor.

[0042] Examples of the reactive group to the amino group or methylol group include a hydroxyl group, a carboxyl group, an amino group, an amide group, an acid anhydride group, an imide group, and an epoxy group. The reactive group-containing acrylic polymer (B-1) may have one or more of these reactive groups. The reaction temperature of the reactive group varies depending on the presence or absence of a catalyst, the pH value, etc., but is preferably 50 to 200° C., more preferably 110 to 170° C. Melamine decorative boards are usually produced at a temperature of 110 to 170° C., so if the reaction temperature is 110 to 170° C., the laminate film of the present invention can be laminated on a melamine substrate and heated, and the laminate film can be sufficiently adhered to the melamine substrate at the same time as the melamine decorative board is produced.

[0043] Examples of monomers having a reactive group include monomers having a hydroxyl group such as (meth)acrylic acid hydroxyalkyl esters; monomers having a carboxyl group such as (meth)acrylic acid, (meth)acryloyloxyalkyl carboxylic acid, and (meth)acryloyloxy aromatic carboxylic acid; monomers having an amino group such as (meth)acrylic acid aminoalkyl esters; monomers having an amide group such as (meth)acrylic acid alkylamide alkyl esters; acid anhydride monomers such as maleic anhydride; maleimide monomers such as maleimide and alkylmaleimide; and epoxy group-containing monomers such as glycidyl (meth)acrylate. These may be used alone or in combination of two or more.

[0044] Among these, from the viewpoint of melamine adhesion after a hot water test when the pressing conditions for lamination to a melamine decorative board are low temperature and short time, monomers having a carboxyl group, an acid anhydride group, or an epoxy group as a reactive group are preferred. Further, a monomer having a carboxyl group or an epoxy group as a reactive group is more preferable because it does not have a hydrolyzable site such as an acid anhydride and can efficiently produce a polymer in an aqueous polymerization such as emulsion polymerization or suspension polymerization. From the viewpoint of preventing crosslinking during melt molding, monomers having a carboxyl group or an acid anhydride group as a reactive group are more preferred.

[0045] Examples of monomers having a carboxyl group as a reactive group include methacrylic acid and acrylic acid. Examples of monomers having an acid anhydride group as a reactive group include maleic anhydride and glutaric anhydride. Maleic anhydride and glutaric anhydride are preferred in terms of preventing the film from having poor appearance due to a crosslinking reaction during melt molding. In the case of maleic anhydride and glutaric anhydride, it is basically necessary to copolymerize aromatic vinyl monomer units, so that methacrylic acid and acrylic acid are preferred from the viewpoint of preventing yellowing after weathering tests. These may be used alone or in combination of two or more.

[0046] The amount of the monomer having a reactive group to be used is preferably 1.5 to 100% by mass based on the reactive group-containing acrylic polymer (B-1), more preferably 2 to 80% by mass, and even more preferably 3 to 30% by mass, from the viewpoints of melamine adhesion and prevention of side reactions. If the amount used is 1.5 mass % or more, the adhesion to melamine becomes better.

[0047] If the amount used is 80% by mass or less, then 20% by mass or more of a non-reactive monomer is used in combination, making it possible to suppress side reactions caused by reactive groups. In addition, when a monomer having a reactive group is water-soluble, dissolution in water can be suppressed by using a water-insoluble monomer in combination, and a polymer can be efficiently produced in aqueous polymerization such as emulsion polymerization or suspension polymerization. If the amount of reactive groups used is increased, the compatibility with (B-2) and (B-3) decreases, and the appearance of the laminated film may deteriorate or the haze value may increase. From the viewpoint of keeping the appearance and haze value of the laminated film low, the amount of reactive groups is preferably as small as possible.

[0048] The amount of the aromatic vinyl monomer used is preferably 0 to 3% by mass based on 100% by mass of the reactive group-containing acrylic polymer (B-1). If the amount used is 3% by mass or less, the weather resistance of the resulting laminate film and melamine decorative board will be good. The amount used is more preferably 0 to 1% by mass, and even more preferably 0 to 0.1% by mass. The amount used is preferably small, and may be 0% by mass.

[0049] As the other monomer, the same monomer as that used for polymerization of the thermoplastic polymer (A-2) can be used. However, from the viewpoints of compatibility with the core-shell rubber (B-2) and the thermoplastic polymer (B-3) and adhesion to the resin layer (I), acrylic monomers, particularly methyl methacrylate, are preferred. The amount of the other monomers used is preferably 0 to 96% by mass, more preferably 20 to 96% by mass, based on the reactive group-containing acrylic polymer (B-1) from the viewpoint of suppressing reactions such as crosslinking caused by the reactive groups. The amount used may be 0% by mass.

[0050] The reactive group-containing acrylic polymer (B-1) can be produced by various polymerization methods such as suspension polymerization, emulsion polymerization, bulk polymerization, solution polymerization, etc. However, when an acid anhydride or a monomer having an imide structure is used as a monomer having a reactive group, hydrolysis occurs during polymerization, so that the polymer cannot be produced by aqueous polymerization such as suspension polymerization or emulsion polymerization. During the polymerization, a chain transfer agent, other polymerization aids, etc. may be used. As the chain transfer agent, mercaptans are preferred.

[0051] The Tg of the reactive group-containing acrylic polymer (B-1) is preferably from 60 to 120°C, more preferably from 60 to 100°C, further preferably from 70 to 98°C, and particularly preferably from 75 to 95°C. If Tg is 60° C. or higher, the heat resistance and water whitening resistance of the melamine decorative board using the laminate film of the present invention will be good, and in particular, the melamine adhesion and whitening resistance will be good after a test of immersion in warm water at 65° C. for 48 hours. In addition, since the blocking property of the film and raw resin is reduced, it is easy to unwind from the film roll and has excellent handleability, and appearance defects due to blocking marks are unlikely to occur, so that a laminate film with excellent appearance quality can be obtained. If the Tg is 120° C. or less, when a melamine decorative board having the laminate film of the present invention laminated thereon is produced, the adhesion between the melamine base material and the laminate film is better even if press processing is performed at a lower temperature, which means that the processing conditions when producing a melamine decorative board having the laminate film laminated thereon are relaxed.

[0052] The Tg can be determined by the Fox equation using the Tg values ​​of the homopolymers of the components constituting the reactive group-containing acrylic polymer (B-1). The Fox equation is shown below. 1 / (273+Tg)=Σ(wi / (273+Tgi)) In the formula, Tg is the Tg (°C) of the copolymer (or a mixture thereof), wi is the mass fraction of monomer i, and Tgi is the Tg (°C) of the homopolymer obtained by polymerizing monomer i.

[0053] Here, the Tg value of the homopolymer is the value given in the POLYMER HANDBOOK THIRD EDITION (WILEY INTERSCIENCE) or the value in the catalogue of the monomer manufacturer. If the monomer contains a crosslinkable monomer, the Tg is determined for the monomer excluding the crosslinkable monomer.

[0054] [Core-shell rubber (B-2)] The core-shell rubber (B-2) is not particularly limited as long as it contains a structural unit derived from a monomer represented by the following formula 1. CH2=C(R1 )COO-R 2 - Formula 1 Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a group selected from a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group.

[0055] Also, the acid value of the core-shell rubber (B-2) is preferably 5 mgKOH / g or more. If the acid value is 5 mgKOH / g or more, good melamine adhesion can be obtained. The acid value is preferably 200 mgKOH / g or less. If the acid value is 200 mgKOH / g or less, the water absorption of the resin composition (B) decreases, and the water whitening resistance of the laminated film and the melamine decorative board laminated with the laminated film is improved. From the viewpoint of adhesion and water whitening resistance, the acid value is preferably 10 mgKOH / g or more, more preferably 15 mgKOH / g or more, and even more preferably 20 mgKOH / g or more. On the other hand, it is more preferably 150 mgKOH / g or less, even more preferably 100 mgKOH / g or less, particularly preferably 80 mgKOH / g or less, and most preferably 50 mgKOH / g or less. The acid value is a value calculated by the method described below. When the core-shell rubber (B-2) is a polymer obtained by polymerizing a monomer represented by the above formula 1, it is converted into a monomer having an acid group by heat treatment, and becomes a core-shell rubber (B-2) satisfying the above acid value. Since the acid value is within the above range, the resin contains structural units derived from monomers having a reactive group to an amino group or a methylol group, and therefore can be bonded to a melamine decorative board by being heated and reacted in contact with a material containing methylol melamine and its derivatives, specifically, the melamine resin of a melamine decorative board or a precursor thereof.

[0056] The amount of the monomer having a reactive group to be used is preferably 1.5 to 100% by mass based on the core-shell rubber (B-2), more preferably 2 to 80% by mass, and further preferably 3 to 30% by mass, from the viewpoints of melamine adhesion and prevention of side reactions. If the amount used is 1.5 mass % or more, the adhesion to melamine becomes better.

[0057] Furthermore, the core-shell rubber (B-2) is preferably an acrylic rubber particle having a multilayer structure of two or more layers in which a layer containing a hard polymer (b-2) is formed as an outer layer on a layer containing an elastic copolymer (b-1) as an inner layer. The acrylic rubber particles preferably have a multi-layer structure of two or more layers, in which a layer containing a hard polymer (b-2) as an outer layer having a structure of one or more layers and obtained by graft polymerization of a monomer mainly composed of a methacrylic acid alkyl ester is formed on a layer containing an elastic copolymer (b-1) as an inner layer having a structure of one or more layers and obtained mainly composed of a (meth)acrylic acid alkyl ester. In particular, from the viewpoint of adhesion to a melamine decorative board, it is preferable that the hard polymer (b-2) contains a core-shell rubber (B-2) containing a structural unit derived from a monomer represented by the following formula 1. CH2=C(R 1 )COO-R 2 - Formula 1 Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a group selected from a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group. The core-shell rubber (B-2) may also have one or more layers containing an intermediate polymer (b-3) between the layer containing the elastic copolymer (b-1) and the layer containing the hard polymer (b-2). The content of the elastic copolymer (b-1) in the core-shell rubber (B-2) is preferably 10 to 90 mass%, more preferably 20 to 70 mass%. The content of the hard polymer (b-2) in the core-shell rubber (B-2) is preferably 10 to 90 mass%, more preferably 30 to 70 mass%. The content of the intermediate polymer (b-3) in the core-shell rubber (B-2) is preferably 0 to 35 mass%, more preferably 0 to 20 mass%. When the content is 35 mass% or less, the balance of the final polymer is good.

[0058] The elastic copolymer (b-1) is preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate. Here, (meth)acrylic acid refers to acrylic acid or methacrylic acid. The elastic copolymer (b-1) is more preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate. The monomer composition may further contain a monomer other than the (meth)acrylic acid alkyl ester and a crosslinkable monomer. For example, the elastic copolymer (b-1) may contain 80 to 100 mass% of an acrylic acid alkyl ester having an alkyl group with 1 to 8 carbon atoms and a methacrylic acid alkyl ester having an alkyl group with 1 to 4 carbon atoms, 0 to 20 mass% of a monomer other than the (meth)acrylic acid alkyl ester, and 0 to 10 mass% of a crosslinkable monomer (total 100 mass%).

[0059] As the alkyl acrylate having an alkyl group having 1 to 8 carbon atoms, for example, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and n-octyl acrylate are preferable, and alkyl acrylates having a low Tg are more preferable. These may be used alone or in combination of two or more.

[0060] The alkyl acrylate is used as a main component of the monomers constituting the elastic copolymer (b-1). Specifically, the amount of the alkyl acrylate used is preferably 30 to 99.9% by mass based on the total monomers constituting the elastic copolymer (b-1). When the amount used is 30% by mass or more, the moldability of the film is good. The amount used is more preferably 50 to 95% by mass. In addition, the range of the amount used indicates the amount of the alkyl acrylate used in the elastic copolymer (b-1) as a whole when the elastic copolymer (b-1) has a structure of two or more layers. For example, when the elastic copolymer (b-1) is made into a hard core structure, the amount of the alkyl acrylate used in the first layer (core) can be less than 30 mass%.

[0061] Examples of methacrylic acid alkyl esters having an alkyl group having 1 to 4 carbon atoms include methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate. These may be used alone or in combination of two or more. The amount of methacrylic acid alkyl ester used is preferably 0 to 69.9% by mass, more preferably 0 to 40% by mass, based on the total monomers constituting the elastic copolymer (b-1).

[0062] Examples of the monomer other than the (meth)acrylic acid alkyl ester include other vinyl monomers copolymerizable with the (meth)acrylic acid alkyl ester. Examples of the monomer other than the (meth)acrylic acid alkyl ester include styrene and acrylonitrile. These may be used alone or in combination of two or more. When using a monomer other than the (meth)acrylic acid alkyl ester, the amount used is preferably 0 to 69.9% by mass, more preferably 0 to 20% by mass, based on the total monomers constituting the elastic copolymer (b-1).

[0063] Examples of the crosslinkable monomer include ethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol dimethacrylate, propylene glycol dimethacrylate, and a graft crosslinking agent. These may be used alone or in combination of two or more. The amount of the crosslinkable monomer used is preferably 0.1 to 10 mass% and more preferably 0.5 to 5 mass% based on the total monomers constituting the elastic copolymer (b-1). From the viewpoint of stability of the core-shell rubber (B-2), it is preferable to use a graft crosslinking agent as the crosslinkable monomer.

[0064] Examples of the graft crosslinking agent include allyl esters, methallyl esters, or crotyl esters of α,β-unsaturated carboxylic acids or unsaturated dicarboxylic acids; triallyl cyanurate, triallyl isocyanurate, etc. Among these, allyl esters of acrylic acid, methacrylic acid, maleic acid, fumaric acid, etc. are preferred, and allyl methacrylate is more preferred because of its excellent effect. Such graft crosslinking agents mainly react and chemically bond with the conjugated unsaturated bond of the ester much faster than the allyl, methallyl or crotyl groups, and most of the allyl, methallyl or crotyl groups, which react slowly, function effectively during the polymerization of the next layer polymer, providing graft bonds between two adjacent layers.

[0065] The rigid polymer (b-2) is preferably a polymer obtained by polymerizing a monomer other than an alkyl methacrylate ester, an alkyl acrylate ester, and an alkyl (meth)acrylate ester. From the viewpoint of adhesion to a melamine decorative board, it is more preferable that the rigid polymer (b-2) contains a monomer represented by the following formula 1. CH2=C(R 1 )COO-R 2 - Formula 1 Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a group selected from a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group. Specific examples of the monomer represented by formula 1 used in the rigid polymer (b-2) include (meth)acrylic acid, (meth)acrylic acid tert-butyl ester, (meth)acrylic acid phenyl ester, (meth)acrylic acid isobornyl ester, etc. Among these, it is preferable to use (meth)acrylic acid and (meth)acrylic acid tert-butyl ester. The rigid polymer (b-2) is preferably obtained by polymerizing 50 to 99% by mass of a linear (meth)acrylic acid alkyl ester and 1 to 50% by mass of a monomer represented by formula 1 in the presence of the elastic copolymer (b-1) based on the total monomers used in the rigid polymer (b-2), more preferably by polymerizing 60 to 99% by mass of a linear (meth)acrylic acid alkyl ester and 1 to 40% by mass of a monomer represented by formula 1, and even more preferably by polymerizing 70 to 99% by mass of a linear (meth)acrylic acid alkyl ester and 1 to 30% by mass of a monomer represented by formula 1. If the monomer represented by formula 1 is 1% by mass or more, the melamine adhesion of the obtained film is improved. Also, if the monomer represented by formula 1 is 20% by mass or less, corrosion of the production equipment is unlikely to occur. The (meth)acrylic acid linear alkyl ester used in the production of the rigid polymer (b-2) is not particularly limited, but from the viewpoints of polymerization reactivity and cost, it is preferable that the alkyl group has a carbon number of 1 to 12. Specific examples thereof include methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, methyl acrylate, n-butyl acrylate, etc., and these monomers may be used alone or in combination of two or more.

[0066] The intermediate polymer (b-3) is preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate ester, an alkyl methacrylate ester, a monomer other than an alkyl (meth)acrylate ester, and a crosslinkable monomer. The intermediate polymer (b-3) is more preferably a polymer obtained by polymerizing a monomer composition containing an alkyl acrylate ester having an alkyl group with 1 to 8 carbon atoms, an alkyl methacrylate ester having an alkyl group with 1 to 4 carbon atoms, a monomer other than an alkyl (meth)acrylate ester, and a crosslinkable monomer. For example, the intermediate polymer (b-3) may contain 10 to 90% by mass of an alkyl acrylate ester having an alkyl group with 1 to 8 carbon atoms, 90 to 10% by mass of an alkyl methacrylate ester having an alkyl group with 1 to 4 carbon atoms, 0 to 20% by mass of a monomer other than an alkyl (meth)acrylate ester, and 0 to 10% by mass of a crosslinkable monomer (total 100% by mass).

[0067] The monomers used in the intermediate polymer (b-3) may be the same as those used in the polymerization of the elastic copolymer (b-1). The content (monomer composition ratio) of the alkyl acrylate in the intermediate polymer (b-3) is preferably lower than that in the elastic copolymer (b-1) and higher than that in the rigid polymer (b-2).

[0068] The average particle size of the core-shell rubber (B-2) is preferably 50 to 300 nm, more preferably 50 to 200 μm, and even more preferably 60 to 100 nm. From the viewpoint of film transparency and film formability, the average particle size is preferably 50 nm or more. The average particle size is a value measured by the method described below.

[0069] The method for producing the core-shell rubber (B-2) is not particularly limited. For example, an emulsion polymerization method can be used as a method for producing the elastic copolymer (b-1) and the rigid polymer (b-2). In addition, they can also be produced by emulsion suspension polymerization, which converts the emulsion polymerization into a suspension polymerization system when polymerizing the polymer constituting the outermost layer after the emulsion polymerization. The polymerization temperature is appropriately selected depending on the type and amount of the polymerization initiator used, and is preferably 40 to 120°C, more preferably 60 to 95°C. As the polymerization initiator, a known polymerization initiator can be used. The polymerization initiator can be added to either one or both of the aqueous phase and the monomer phase.

[0070] Examples of emulsifiers that can be used in emulsion polymerization include anionic, cationic, and nonionic surfactants, with anionic surfactants being preferred. Examples of anionic surfactants include carboxylate-based surfactants such as potassium oleate, sodium stearate, sodium myristate, sodium N-lauroyl sarcosinate, and dipotassium alkenyl succinate; sulfate-based surfactants such as sodium lauryl sulfate; sulfonate-based surfactants such as sodium dioctyl sulfosuccinate, sodium dodecylbenzenesulfonate, and sodium alkyl diphenyl ether disulfonate; and phosphate-based surfactants such as sodium polyoxyethylene alkyl phenyl ether phosphate. These may be used alone or in combination of two or more.

[0071] The polymer latex obtained by emulsion polymerization can be filtered, for example, with a filter having an opening of 100 μm or less, and then separated and recovered by a method such as an acid coagulation method, a salt coagulation method, a freeze coagulation method, or a spray drying method. In the acid coagulation method, inorganic acids such as sulfuric acid, hydrochloric acid, and phosphoric acid, and organic acids such as acetic acid can be used. In the salt coagulation method, inorganic salts such as sodium sulfate, magnesium sulfate, aluminum sulfate, and calcium chloride, and organic salts such as calcium acetate and magnesium acetate can be used. From the viewpoint of the flow characteristics of the obtained powder, calcium chloride is preferred. These may be used alone or in combination of two or more. The separated and recovered polymer is further washed, dehydrated, dried, and the like to obtain a core-shell rubber (B-2).

[0072] [Thermoplastic polymer (B-3)] The thermoplastic polymer (B-3) may be any resin other than the reactive group-containing acrylic polymer (B-1) and the core-shell rubber (B-2), and may be the same as the thermoplastic polymer (A-2).

[0073] [Additives (B-4)] The additive (B-4) is a compound other than the reactive group-containing acrylic polymer (B-1), the core-shell rubber (B-2) and the thermoplastic polymer (B-3), and may be the same as the additive (A-3) used in preparing the acrylic resin composition (A).

[0074] [Laminated film] The thickness of the laminated film of the present invention is preferably from 10 to 100 μm, more preferably from 20 to 80 μm, and even more preferably from 25 to 40 μm. If the thickness is 10 μm or more, the laminate film can be easily produced, and the resulting melamine decorative board can be imparted with sufficient weather resistance. If the thickness is 100 μm or less, the laminated film has a suitable flexibility, so that peeling can be prevented when the resulting melamine decorative board is cut. It is also economically advantageous in terms of mass per unit area. Furthermore, the film forming properties are stable, making it easy to manufacture the laminated film. Furthermore, when laminated on a melamine decorative board, the pencil hardness of the decorative board increases, improving scratch resistance.

[0075] The thickness of the resin layer (I) is preferably from 1 to 99.5 μm, more preferably from 5 to 50 μm, and further preferably from 20 to 50 μm. If the thickness of the resin layer (I) is 1 μm or more, the weather resistance and water whitening resistance of the resulting melamine decorative board are good. Also, if the thickness of the resin layer (I) is 99.5 μm or less, it is economically advantageous in terms of mass per unit area.

[0076] The thickness of the resin layer (II) is preferably from 0.5 to 99 μm, more preferably from 2 to 10 μm, further preferably from 3 to 10 μm, particularly preferably from 3 to 7 μm. If the thickness of the resin layer (II) is 0.5 μm or more, the adhesion to melamine is improved, and if the thickness of the resin layer (II) is 99 μm or less, it is economically advantageous in terms of the mass per unit area.

[0077] The laminated film of the present invention may have a layer other than the above-mentioned surface layer (hereinafter, intermediate layer), and a known resin may be used as the intermediate layer. For example, compositions such as polyvinyl chloride resin, polycarbonate resin, ABS resin, AS resin, MBS resin, MS resin, styrene resin, methacrylic resin, polyglutarimide, glutaric anhydride polymer, lactone cyclized methacrylic resin, polyvinylidene fluoride, fluorine resin, polyethylene terephthalate resin, polybutylene terephthalate resin, TPO resin, polyethylene resin, and polypropylene resin are exemplified, and from the viewpoint of compatibility with the resin layer (I) and the resin layer (II), acrylic resin and fluorine resin are more preferable.

[0078] The number of intermediate layers is preferably 3 or less, and more preferably 2 or less. If the number of layers is more than 3, it becomes difficult to form the film. There may be cases where this is necessary.

[0079] The haze of the laminated film of the present invention is preferably 20% or less, more preferably 10% or less. If the haze is 20% or less, for example, when the laminated film is used for protecting a decorative plate, the pattern of the underlying decorative layer does not become cloudy, and a decorative plate having excellent design can be obtained.

[0080] [Laminated film manufacturing method] As a method for producing the laminated film of the present invention, from the viewpoint of productivity, a method of forming a laminated structure of the resin layer (I) and the resin layer (II) by co-extrusion through a feed block die or a multi-manifold die is preferred. Alternatively, a method of forming the resin layer (I) and the resin layer (II) into a film shape by melt extrusion using a T-die or the like, and laminating the two kinds of films by a thermal lamination method can also be used. Furthermore, an extrusion lamination method can be used in which one resin layer is formed into a film, and then the other resin layer is laminated by melt extrusion. When melt extrusion is performed, the resin composition in a molten state can be extruded while being filtered through a screen mesh of 200 mesh or more in order to remove nuclei and impurities that may cause surface defects.

[0081] The extruder used for producing pellets is preferably one with one or more vents. This is because heating the resin composition (B) causes the acid to become anhydride, generating water and / or methanol and / or decomposition products, which can be removed through the vent to prevent poor appearance due to foaming during film production. The extruder used may be a single-screw or multi-screw extruder. For the same reason, it is preferable to use an extruder with a vent for film production.

[0082] Furthermore, in order to prevent foaming and thermal deterioration of the resin composition (B), it is preferable to use a coating method in which a solution containing the resin composition (B) is applied onto the resin layer (I) formed into a film to laminate the resin layer (II). For example, a method in which a solution in which the resin composition (B) is dissolved in a solvent such as an organic solvent is applied onto the resin layer (I) by a printing method such as gravure printing, screen printing, or offset printing, or a coating method such as a blade coating or rod coating, and then the solution is dried by heating to remove the solvent can be mentioned. In addition, a solution containing the acrylic resin composition (A) may be applied onto the resin layer (II) formed into a film to laminate the resin layer (I).

[0083] Examples of the solvent include alcohol-based solvents such as methanol and ethanol; aromatic solvents such as xylene and toluene; aliphatic hydrocarbon-based solvents such as hexane and pentane; halogenated hydrocarbon-based solvents such as chloroform and carbon tetrachloride; phenol-based solvents such as phenol and cresol; ketone-based solvents such as methyl ethyl ketone and methyl isobutyl ketone; ether-based solvents such as diethyl ether and methoxytoluene; fatty acid-based solvents such as formic acid and acetic acid; acid anhydride-based solvents such as acetic anhydride; ester-based solvents such as ethyl acetate and n-propyl acetate; nitrogen-containing solvents such as dimethylformamide and dimethylacetamide; sulfur-containing solvents such as thiophene and dimethyl sulfoxide; solvents having two or more functional groups such as diacetone alcohol and 2-methoxyethanol (methyl cellosolve), and water. Among these, dimethylformamide and dimethylacetamide are preferred from the viewpoint of dissolving power. These may be used alone or in combination of two or more.

[0084] Depending on the printability or coatability as a paint, additives for improving solution properties such as anti-skinning agents, thickeners, anti-settling agents, anti-sagging agents, defoamers, leveling agents, etc. may be added to the resin composition. Furthermore, additives for improving coating film performance such as extender pigments, light stabilizers, ultraviolet absorbers, antioxidants, antibacterial agents, antifungal agents, flame retardants, etc. may be added to the resin composition.

[0085] [Surface protection film for melamine decorative boards, melamine decorative boards] The laminated film of the present invention has excellent adhesiveness and can be adhered to various substrates, so it can be suitably used as a protective film. In particular, the laminated film of the present invention exhibits excellent adhesiveness (melamine adhesion) to melamine resin, so it can be suitably used as a surface protective film for melamine decorative boards. In addition, the protective film for melamine decorative boards of the present invention has excellent water whitening resistance, so it is suitable for outdoor use.

[0086] Melamine decorative boards are used on horizontal surfaces such as desks and counters, and on vertical surfaces such as walls, and their configuration and manufacturing method are described in detail in the Decorative Board Handbook (published by the New Construction Materials Research Institute in 1973), etc. These melamine decorative boards are obtained, for example, by impregnating decorative paper for decorative boards with melamine resin, laminating the dried melamine resin-impregnated paper and resin-impregnated core paper, which is the core material layer, and, if necessary, impregnating overlay paper with melamine resin in order to protect the pattern of the decorative paper, laminating the dried melamine resin-impregnated overlay paper and balance paper as the bottom layer in order to suppress warping, and thermocompressing the resulting product.

[0087] The melamine resin-impregnated paper may be, for example, a decorative paper for decorative boards impregnated with melamine-formaldehyde resin and dried. The resin-impregnated core paper may be, for example, a core paper for decorative boards impregnated with a resin liquid mainly composed of phenol-formaldehyde resin, melamine-formaldehyde resin, or a mixture thereof, and a slurry containing an inorganic filler such as aluminum hydroxide or calcium carbonate, and dried. The thermocompression molding can be carried out, for example, by laminating a resin-impregnated core paper and a melamine resin-impregnated paper (melamine base material) with the laminate film of the present invention, under conditions of a temperature of 110 to 170° C., a pressure of 5 to 10 MPa, and a time of 10 to 90 minutes.

[0088] When the laminated film of the present invention is laminated to a melamine substrate, it is preferable to heat-seal the film so that the resin layer (II) made of the resin composition (B) faces the melamine substrate. According to this method, lamination can be performed without using an adhesive or a pressure-sensitive adhesive. Lamination can be performed continuously or discontinuously, for example, by a discontinuous lamination method using a heat press method. In particular, when preparing a melamine decorative board, if the melamine substrate and the laminated film of the present invention are laminated and then heat-pressed, the laminated film can be laminated at the same time as the melamine decorative board is prepared, which is advantageous because it reduces the number of steps. Furthermore, if the laminated film of the present invention is used, it has excellent adhesion after a hot water test even if the pressing conditions when laminating the film to the melamine decorative board are low temperature and short time, so it is industrially advantageous.

[0089] On the other hand, if the laminated film of the present invention is not used and, for example, a film consisting of only the resin layer (I) is used, the adhesion to the melamine substrate is low, making it necessary to use an adhesive or primer, which increases costs and significantly reduces productivity. In contrast, when the laminated film of the present invention is used, it is not necessary to use an adhesive or a primer, so that the number of steps can be reduced and costs can be reduced, which is industrially advantageous. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass." The abbreviations in the examples are as follows.

[0091] MMA: Methyl methacrylate MA: Methyl acrylate BA: Butyl acrylate HPMA: 2-Hydroxypropyl methacrylate MAA: Methacrylic acid St: styrene AMA: Allyl methacrylate BDMA: 1,3-butylene glycol dimethacrylate CHP: Cumene hydroperoxide tBH: t-butyl hydroperoxide LPO: Lauryl peroxide nOM: n-octyl mercaptan RS610NA: mono-n-dodecyloxytetraoxyethylene sodium phosphate (product name: "Phosphanol RS-610NA", manufactured by Toho Chemical Industry Co., Ltd.) LA31: ADEKA Corporation, "ADEKA STAB LA-31RG" (product name) 2020: BASF, "Chimassorb2020" (product name) R976: AEROSIL R976 (product name) manufactured by Nippon Aerosil 1076: BASF, "Irganox1076" (product name) VH5: Methacrylic resin (PMMA), manufactured by Mitsubishi Chemical Corporation, "ACRYPET VH5001" (product name) MD: Mitsubishi Rayon Co., Ltd., "ACRYPET MD001" (product name)

[0092] In the examples, various physical properties were measured according to the following methods.

[0093] (1) Acid value The acid value of the reactive group-containing acrylic polymer (B-1) or the core-shell rubber (B-2) was determined by the following method. First, 0.4 g of the sample was dissolved in 50 ml of propylene glycol monomethyl ether and stirred at 65°C for 3 hours. Then, 50 ml of a mixed solvent of acetone / ethanol was added and subjected to neutralization titration. Titration was performed with 0.1 mol / L ethanolic potassium hydroxide solution using phenolphthalein as an indicator. In addition, a blank test was performed in the same manner except that no sample was used, and the acid value was calculated from the following formula. Acid value=(AB)×f×56.1×0.1 / S f: Potency of 0.1 mol / L ethanolic potassium hydroxide S: Sample size (g) A: Amount of ethanolic potassium hydroxide used in titration (ml) B: Amount of ethanolic potassium hydroxide used in the blank test (ml) The calculated acid value of the resin composition (B) is a value calculated from the weight ratio of the reactive group-containing acrylic polymer (B-1) or the core-shell rubber (B-2) in the resin composition (B).

[0094] (2) Mass average molecular weight (Mw) The mass average molecular weight (Mw) of the polymer was determined by the following method. A sample prepared by dissolving the polymer in tetrahydrofuran was subjected to measurement at a temperature of 40° C. using gel permeation chromatography (model name: “HLC-8200”, manufactured by Tosoh Corporation), columns (product name: “TSK-GEL SUPER MULTIPORE HZ-H”, manufactured by Tosoh Corporation, inner diameter 4.6 mm×length 15 cm×2 columns), and an eluent (tetrahydrofuran). The mass average molecular weight (Mw) was determined from a calibration curve using standard polystyrene.

[0095] (3) Glass transition temperature (Tg) The glass transition temperature of the polymer was calculated from the Fox formula using the values ​​given in the Polymer Handbook (J. Brandrup, Interscience, 1989) or the catalog values ​​of the monomer manufacturers.

[0096] (4) Average particle size The average particle size of the core-shell rubber was measured by measuring the final particle size of the polymer latex obtained by emulsion polymerization using a light scattering photometer (product name: "DLS-700", manufactured by Otsuka Electronics Co., Ltd.) by dynamic light scattering method.

[0097] (5) Gel fraction 50 ml of acetone was added to 0.5 g of the obtained resin composition (B) and stirred at 65 ° C for 4 hours. Then, it was centrifuged at 4 ° C and 14000 rpm for 30 minutes, and after removing the supernatant, 50 ml of acetone was added again and centrifuged again under the same conditions. After removing the supernatant, the precipitated gel part was vacuum dried for 8 hours and the mass was measured, and the gel fraction was calculated by the following formula. Gel fraction (%) = (mass of gel part (g) / 0.5) x 100

[0098] (6) Thickness of resin layers (I) and (II) The laminated film was cut into a suitable size, and the thicknesses of the resin layers (I) and (II) were measured using a reflection spectroscopic film thickness meter FE3000 (product name, manufactured by Otsuka Electronics Co., Ltd.).

[0099] (7) Total light transmittance (TT), haze, yellowness index (YI), color difference and whiteness (W(Lab)) The total light transmittance (TT) of the obtained laminated film was evaluated in accordance with JIS K7361-1, the haze value (Haze) in accordance with JIS K7136, the yellowness index (YI) in accordance with JIS K7373, the color difference in accordance with JIS K5600-4-6, and the whiteness (W(Lab)) in accordance with JIS Z8715.

[0100] (8) Melamine base endothermic peak temperature Using a DSC6200 (product name, manufactured by SII Nanotechnology), the endothermic peak temperature was measured when the melamine base material was heated from 25°C to 200°C at a rate of 10°C / min under a nitrogen flow, and the first endothermic peak temperature was taken as the melamine base material endothermic peak temperature.

[0101] (9) Evaluation of hot water whitening resistance Using the obtained melamine decorative board, a boiling test was carried out at 100° C. for 2 hours in accordance with CEN (European Committee for Standardization) standard EN438-2, and the change in whiteness before and after the boiling test was measured.

[0102] (10) Evaluation of resistance to whitening in hot water Using the obtained melamine decorative board, a hot water immersion test was carried out at 65° C. for 48 hours in accordance with CEN (European Committee for Standardization) standard EN438-2, and the change in whiteness before and after the hot water test was measured.

[0103] (11) Adhesion evaluation (adhesion) A checkerboard pattern of 100 squares spaced 1 mm apart was made with a cutter knife on a melamine decorative panel at room temperature, and peelability was checked with cellophane tape (manufactured by Nichiban Co., Ltd.). This test was performed in the initial state, after the boiling test, and after the hot water test, and was classified as follows: if no mass peeled off at all, it was classified as 0; if less than 5% of the mass peeled off, it was classified as 1; if less than 15% of the mass peeled off, it was classified as 2; if less than 35% of the mass peeled off, it was classified as 3; if less than 65% of the mass peeled off, it was classified as 4; and if 65% or more of the mass peeled off, it was classified as 5.

[0104] (12) Maximum height (Rz) Using a surface roughness measuring instrument (manufactured by Tokyo Seimitsu Co., Ltd., product name: SURFCOM 1400D), the maximum height Rz of the resin layer (I) side of the laminated film was measured in accordance with JIS B0601-2001 under conditions of a measurement length of 4.0 mm, an evaluation length of 4.0 mm, a cutoff wavelength of 0.8 mm, and a measurement speed of 0.3 mm / s. The maximum height Rz is calculated by extracting a portion of the roughness curve measured with a roughness meter over a reference length, and expressing the value in micrometers (μm) as the sum of the highest part (maximum peak height: Rp) and the deepest part (maximum valley depth: Rv).

[0105] (13) Storage modulus After preparing a single-layer film (thickness 45 μm) consisting of the resin layer (I), a test piece was cut into a width of 6 mm and a length of 20 mm, and measured using an EXSTAR DMS6100 manufactured by Seiko Instruments Inc. in a tensile mode under the conditions of a heating rate of 2°C / min, a measurement frequency of 0.1 Hz, and a measurement temperature of 100°C.

[0106] <Production Example 1: Production of Core-Shell Rubber (A-1A)> In a nitrogen atmosphere, 206 parts of deionized water was placed in a reaction vessel equipped with a reflux condenser, and the temperature was raised to 80°C. The component (i) shown below was added, and 1 / 10 of the raw material (ii) shown below (a part of the raw material for the elastic copolymer (a-1)) was charged while stirring, and the mixture was held for 15 minutes. Next, the remaining raw material (ii) was continuously added so that the increase rate of the monomer mixture relative to the water was 8% by mass / hour. The mixture was then held for 1 hour to polymerize, and a polymer latex was obtained. Next, 0.2 parts of sodium formaldehyde sulfoxylate was added to the polymer latex. The mixture was then held for 15 minutes, and while stirring at 80°C under a nitrogen atmosphere, the raw material (iii) shown below (a part of the raw material for the elastic copolymer (a-1)) was continuously added so that the increase rate of the monomer mixture relative to the water was 4% by mass / hour. The mixture was then held for 2 hours to polymerize, and a latex of the elastic copolymer (a-1) was obtained.

[0107] 0.2 parts by mass of sodium formaldehyde sulfoxylate was added to the latex of the elastic copolymer (a-1). After that, the mixture was held for 15 minutes, and while stirring at 80°C under a nitrogen atmosphere, the raw material (iv) (raw material for the rigid polymer (a-2)) shown below was continuously added so that the increase rate of the monomer mixture relative to water was 10% by mass / hour. The mixture was then held for 1 hour to polymerize, and a latex of the core-shell rubber (A-1A) was obtained. The average particle diameter of the core-shell rubber (A-1A) was 280 nm.

[0108] This core-shell rubber (A-1A) latex was filtered through a filter with a mesh size of 50 μm, and then subjected to coagulation, aggregation, and solidification reactions using calcium acetate, followed by filtration, washing with water, and drying to obtain a core-shell rubber (A-1A).

[0109] (i) Sodium formaldehyde sulfoxylate 0.4 parts Ferrous sulfate 0.00004 parts Disodium ethylenediaminetetraacetate 0.00012 parts (ii) MMA 11.25 BA 12.5 Division St 1.25 part AMA 0.094 parts BDMA 0.75 part tBH 0.044 parts RS610NA 0.75 part (iii) BA 30.9 Division St 6.6 part AMA 0.66 parts BDMA 0.09 part CHP 0.11 part RS610NA 0.6 parts (iv) MMA 35.6 MA 1.9 part nOM 0.11 parts tBH 0.06 parts

[0110] <Production Example 2: Production of Thermoplastic Polymer (A-2A)> 200 parts of nitrogen-substituted ion-exchanged water was charged into a reaction vessel, and 1 part of potassium oleate and 0.3 parts of potassium persulfate were charged as emulsifiers. Then, 40 parts of MMA, 10 parts of BA, and 0.005 parts of nOM were charged, and the mixture was stirred at 65°C under a nitrogen atmosphere for 3 hours to complete the polymerization. Then, a monomer mixture consisting of 48 parts of MMA and 2 parts of BA was added dropwise over 2 hours, and after completion of the dropwise addition, the mixture was maintained for 2 hours to complete the polymerization. The obtained latex was added to a 0.25% by mass aqueous sulfuric acid solution to cause coagulation, followed by filtration, washing with water, and drying to obtain a thermoplastic polymer (A-2A). The resulting thermoplastic polymer (A-2A) had an Mw of 1,000,000.

[0111] <Production Example 3: Production of acrylic resin composition (A1)> In Production Example 3, 76 parts of VH5 and 2 parts of (A-2A) were blended as the thermoplastic polymer (A-2) with 24 parts of the core-shell rubber (A-1A). 2.36 parts of LA31, 0.45 parts of 2020, 0.3 parts of R976, and 0.1 parts of 1076 were added as additives (A-3) and mixed using a Henschel mixer. Next, this was melt-kneaded and pelletized using a 35 mmφ screw-type twin-screw extruder (L / D=26) under conditions of a cylinder temperature of 200 to 240°C and a die temperature of 240°C to obtain an acrylic resin composition (A1) for the resin layer (I). The gel fraction of the acrylic resin composition (A1) was 21%, and the acid value was 1.6 mgKOH / g. In addition, the storage modulus of the single layer film (thickness 45 μm) consisting of the resin layer (I) obtained using the acrylic resin composition (A1) was 728 MPa.

[0112] <Production Example 4: Production of reactive group-containing polymer (B-1A)> In Production Example 4, a mixture of the following components was placed in a reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen gas inlet, and the like. MMA 80th Division BA 5th Division HPMA 15 copies nOM 0.25 parts LPO 0.4 parts Methyl methacrylate / methacrylate salt / methacrylate ethyl sulfonate copolymer 0.02 parts Sodium sulfate 0.3 parts 145 parts deionized water

[0113] The inside of the vessel was thoroughly replaced with nitrogen gas, and then the vessel was heated to 75°C while stirring, and the polymerization reaction was allowed to proceed in a nitrogen gas stream. After 2 hours, the temperature was raised to 95°C and maintained for an additional 60 minutes to complete the polymerization. The resulting polymer beads were dehydrated and dried to obtain a reactive group-containing polymer (B-1A). The resulting reactive group-containing polymer (B-1A) had an Mw of 96,800, a Tg of 78°C, and an acid value of 0.3 mgKOH / g.

[0114] <Production Example 5: Production of Core-Shell Rubber (B-2A)> A vessel equipped with a stirrer was charged with 8.5 parts of deionized water, and then the following component (ii) was added thereto with stirring, followed by stirring for 20 minutes to prepare an emulsion. Next, 191.5 parts of deionized water was placed in a polymerization vessel equipped with a cooler, and the temperature was raised to 60° C. under nitrogen. Next, the following component (i) was added dropwise to the polymerization vessel over a period of 2 minutes with stirring, and the reaction was continued for 15 minutes. Next, the following component (iii) was added dropwise to the polymerization vessel over 100 minutes, and the reaction was continued for 60 minutes to obtain a latex. The elastic copolymer alone had a Tg of -45°C.

[0115] Next, the following component (iv) was dropped into the polymerization vessel over 150 minutes, and the reaction was continued for 30 minutes to form a hard polymer on the elastic copolymer. Through the above steps, a latex containing 100 parts of core-shell rubber (B-2A) was obtained. The Tg of the hard polymer alone was 75°C. The average particle size of the core-shell rubber (B-2A) measured after polymerization was 82 nm. The latex of the core-shell rubber (B-2A) was filtered through a filter with a mesh size of 50 μm, and then coagulated with calcium chloride, filtered, washed with water, and dried to obtain the core-shell rubber (B-2A).

[0116] (i) Sodium formaldehyde sulfoxylate 0.2 parts Ferrous sulfate 0.0001 parts Disodium ethylenediaminetetraacetate 0.0003 parts (ii) MMA 0.3 Division BA 4.5 Division AMA 0.085 parts CHP 0.025 part Perex OTP 1.0 parts (iii) MMA 4.0 Division BA 36.0 Division AMA 0.68 parts CHP 0.04 part (iv) MMA 35.2 MAA 9.9 parts BA 9.9 Division nOM 0.22 parts tBH 0.069 parts

[0117] <Production Example 6: Production of Core-Shell Rubber (B-2B)> In a nitrogen atmosphere, 153 parts of deionized water was placed in a reaction vessel equipped with a reflux condenser and heated to 80° C. The following component (i) was added, and while stirring, the following component (ii) was added. The mixture was then maintained for 1 hour to polymerize, yielding a polymer latex. Next, 0.1 parts of sodium formaldehyde sulfoxylate was added to the polymer latex. After that, the mixture was held for 15 minutes, and the following component (iii) was added while stirring at 80°C under a nitrogen atmosphere. The mixture was then held for 1 hour to polymerize, and a latex of core-shell rubber (B-2B) was obtained. The average particle size of the core-shell rubber (B-2B) was 120 nm. The latex of the core-shell rubber (B-2B) was filtered through a filter with a mesh size of 50 μm, and then coagulated with calcium acetate, filtered, washed with water, and dried to obtain the core-shell rubber (B-2B).

[0118] (i) Sodium formaldehyde sulfoxylate 0.4 parts Ferrous sulfate 0.00004 parts Disodium ethylenediaminetetraacetate 0.00012 parts (ii) BA 50.9 Division St 11.6 part AMA 0.56 parts tBH 0.19 parts RS610NA 1.0 part (iii) MMA 35.6 MA 1.9 part tBH 0.056 parts nOM 0.16 parts RS610NA 0.25 part

[0119] <Production Example 7: Production of thermoplastic polymer (B-3A)> The thermoplastic polymer (B-3A) used was the same as the thermoplastic polymer (A-2A).

[0120] <Production Example 8: Production of resin composition (B1)> In Production Example 8, 53 parts of MD and 2 parts of (B-3A) were blended as the thermoplastic polymer (B-3) with 47 parts of the core-shell rubber (B-2B). A resin composition (B1) for the resin layer (II) was obtained in the same manner as in Production Example 3, except that 2.1 parts of LA31, 0.45 parts of 2020, and 0.1 parts of 1076 were added as additives (B-4). The gel fraction of the resin composition (B1) was 28%, the acid value was 29.4 mg KOH / g, and the adhesive functional group content was 4.7% by mass.

[0121] <Production Example 9: Production of resin composition (B2)> In Production Example 9, 2 parts of (B-3A) were blended as the thermoplastic polymer (B-3) with 60 parts of the reactive group-containing polymer (B-1A) and 40 parts of the core-shell rubber (B-2A). A resin composition (B2) for the resin layer (II) was obtained in the same manner as in Production Example 3, except that 2.1 parts of LA31, 0.45 parts of 2020, and 0.1 parts of 1076 were added as additives (B-4). The gel fraction of the resin composition (B2) was 34%, the acid value was 0.2 mgKOH / g, and the adhesive functional group content was 9.0 mass%.

[0122] <Examples 1-2: Preparation of laminated film and melamine decorative board> In Example 1, the acrylic resin composition (A1) for the resin layer (I) obtained in Production Example 3 and the resin composition (B1) for the resin layer (II) obtained in Production Example 8 were dried at 80°C for one day. (B1) was plasticized in a 30 mmφ extruder with a cylinder temperature set at 230° C. In addition, the acrylic resin composition (A1) was plasticized in a 40 mmφ extruder equipped with a 400 mesh screen mesh with a cylinder temperature set at 240° C. Next, a 50 μm thick resin laminate film was formed using a two-type two-layer feed block die set at 240° C. The thicknesses of the resin layers (I) and (II) were 45 μm and 5 μm, respectively. The results of the total light transmittance (TT), haze, yellowing index (YI), and maximum height Rz of the obtained laminate film are summarized in Table 1.

[0123] Furthermore, a melamine substrate was laminated on the resin layer (II) side of this laminated film, and both sides were sandwiched between mirror-finished stainless steel plates, and pressed at a temperature of 140°C, a pressure of 3 MPa, and a time of 10 minutes to produce a melamine decorative board. The results of adhesion and whiteness of the obtained melamine decorative board after a water resistance test are shown in Table 1. The endothermic peak temperature of the melamine substrate used was 100°C.

[0124] [Table 1]

[0125] In Example 2, a laminate film and a melamine decorative board were produced in the same manner as in Example 1, except that the materials shown in Table 1 were used and the thicknesses of the resin layers (I) and (II) were set as shown in Table 1. The evaluation results of the obtained melamine decorative board are shown in Table 1.

[0126] <Comparative Example 1> A laminate film and a melamine decorative board were produced in the same manner as in Example 1, except that the materials shown in Table 1 were used and the thicknesses of the resin layers (I) and (II) were set as shown in Table 1. The evaluation results of the obtained melamine decorative board are shown in Table 1.

[0127] The above examples and production examples have revealed the following. The laminated films obtained in Examples 1 and 2 have excellent adhesion to melamine substrates. Furthermore, it is possible to obtain melamine decorative boards that have good adhesion after boiling tests, have a small increase in whiteness, and are excellent in water whitening resistance. Furthermore, they have excellent transparency and are highly valuable industrially.

[0128] On the other hand, the film obtained in Comparative Example 1 had poor adhesion to melamine because the core-shell rubber did not contain a structural unit derived from the monomer represented by formula 1.

[0129] Although the present invention has been described above with reference to the embodiments and examples, the present invention is not limited to the above-mentioned embodiments and examples. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.

Claims

1. A surface protecting film for melamine decorative boards, comprising a resin layer (II) made of a resin composition (B), the resin composition (B) containing a core-shell rubber (B-2) containing a structural unit derived from a monomer represented by the following formula 1: CE 2 = C (R 1 )COO-R 2 - Formula 1 Here, R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or a group selected from a tertiary hydrocarbon group, an aromatic hydrocarbon group, and an alicyclic hydrocarbon group.

2. The surface protecting film for melamine decorative boards according to claim 1, wherein the acid value of the resin composition (B) is 5 mg KOH / g or more.

3. The surface protecting film for melamine decorative boards according to claim 1, further comprising a resin layer (I) made of an acrylic resin composition (A) having an acid value of less than 5 mg KOH / g.

4. The surface protecting film for melamine decorative boards according to claim 3, wherein the maximum height Rz of the resin layer (I) is 0.15 μm or more.

5. The surface protecting film for melamine decorative boards according to claim 3, wherein the content of the antiblocking agent in 100% by mass of the acrylic resin composition (A) is 0.01 to 2% by mass.

6. The surface protecting film for melamine decorative boards according to claim 3, wherein the thickness of the resin layer (II) is 3 to 10 μm.

7. The surface protecting film for melamine decorative boards according to claim 3, wherein the acrylic resin composition (A) contains a core-shell rubber, and the particle size of the core-shell rubber is 100 nm or more.

8. A melamine decorative board comprising the surface protective film for melamine decorative boards according to any one of claims 3 to 7 and a melamine substrate laminated in the order of resin layer (I), resin layer (II) and melamine substrate.

Citation Information

Patent Citations

  • Core-shell type emulsion

    JP1998251312A

  • Method for producing aqueous dispersion of latex particles having heterogeneous morphology, latex particles obtained by this method, dispersion, redispersible powder, and use thereof

    JP2002521507A

  • Thermoplastic resin film and production method thereof

    JP2008239739A

  • Acrylic resin film

    JP2013103385A

  • Resin laminate film and method for producing the same, and melamine decorative

    JP2017200758A